"Do Books Like These Have Authors?" New Roles for Text and New Demands on Students in Integrated Science‐Literacy Instruction. Issue 1 (January 2015) - SØRVIK, GARD OVE; BLIKSTAD‐BALAS, MARTE; ØDEGAARD, MARIANNE
ABSTRACT We report on research that explores students' literacy practices in six Norwegian primary school science classrooms during integrated science‐literacy instruction. The study combines observational video data and interview data to examine students' encounters with and use of text, along with their views and experiences related to science and science text. Drawing on New Literacy Studies perspectives—seeing literacy as a situated social practice—our analysis reveals how multiple literacies emerged in the context of integrated science‐literacy instruction, where elements of students' informal literacies became valued resources in the dialogic process of inquiry. More specifically, the students engaged in literacy practices that transcended the contexts of science and school science to incorporate texts and literacy practices from the students' everyday lives as well as practices that were confined to a school‐only context. On the basis of their talk about text in the classroom and data from focus group interviews, we also identify some of the challenges that these students faced in their encounters with science texts in this setting.